Membangun Kepemimpinan Otentik dengan Model Penugasan - Arcadius Benawa (Bina Nusantara University, 2013)
Bina Nusantara (Binus) University as education organization has to improve itself to realize its motto ”People, Innovation, Excellence”. That’s why Binus University have to implement the open system. By open system, BINUS University realizes practicability, flexibility, and openess. If it is done, BINUS University can guarantee to achieve its goal effectively and efficiently. Because of this, system approach is very important for the students as leaders in the next day who understand and make solution in overcome the complexity of problems in their organization. Everyone realizes that there is no problem like an island in itself. The problem is always linked with others. That’s why, the problem should be understood as a system which has some sub-systems. And every problem should be overcome by system approach, which accomodate wholistic approach and understand multifactors in it. In the learning process, assignment model used makes it effective or not in the system management, especially in education system in BINUS UNIVERSITY. By this reason, Eriksen’s ”Authentic Leadership: Practical Reflexivity, Self-Awareness, and Self-Authorship” (2009) very inspires the writer.